Urban Cat Management in Australia—Evidence-Based Strategies for Success - Jennifer Cotterell; Jacquie Rand; Rebekah Scotney (Animals)
Urban free-roaming cats present challenges like noise, urination, defecation, property damage, public health risks, and wildlife predation. Traditional enforcement methods, such as containment laws and impounding, are ineffective, especially in low-income areas, where many free-roaming cats live. These cats are often cared for by “semi-owners”, who feed them without formal ownership. Financial barriers to sterilization for owned and semi-owned cats in these areas result in unplanned litters, sustaining the free-roaming population and burdening local authorities and animal welfare organizations. Cats causing complaints are frequently impounded and euthanized, affecting the mental health of veterinary, shelter, and council staff. This paper critiques punitive, compliance-driven strategies and highlights the success of assistive Community Cat Programs offering free sterilization, microchipping, and registration. In Banyule, Victoria, such a program reduced cat impoundments by 66%, euthanasia by 82%, and complaints by 36% between 2013 and 2021. Two other programs in large cities and rural towns in NSW and a rural town in Queensland have now reported similar results. Based on the One Welfare framework, these programs address the interconnectedness of animal welfare, human well-being, and environmental health. By removing financial barriers, they build trust between authorities and caregivers, improving compliance and welfare for cats, communities, and wildlife. However, following the loss of key program staff and the reintroduction of financial barriers in Banyule, cat intake rose by 140% between 2022 and 2024, demonstrating the detrimental impact of financial barriers and punitive approaches. This underscores the importance of sustained, community-based solutions and legislative reforms that prioritize humane, barrier-free strategies. Understanding the critical success factors for Community Cat Programs is essential for effective cat management.